Predicting recovery after intracerebral hemorrhage: an external validation in patients from controlled clinical trials - Weimar, Christian; Ziegler, Andreas; Sacco, Ralph L.; Diener, Hans C.; König, Inke R.; Hennerici, Michael G. (Journal of neurology, 2009)
An early and reliable prognostic indication in stroke patients is potentially useful for initiation of individual treatment and for informing patients and relatives. We recently developed a regression model as well as a simple 11-point predictive score (Essen ICH score) for functional recovery within three months after acute intracerebral hemorrhage (ICH) based on age and the National Institutes of Health Stroke Scale (NIH-SS). Here, we demonstrate the applicability of our models in an independent sample of ICH patients from controlled clinical trials.
VISTA Steering Committee members: Lees KR (chair), Hacke W, Sacco RL, Diener HC, Grotta J, Lyden P, Donnan GA, Davis SM, Bath PMW, Wahlgren NG, Hennerici M, Kaste M, Hommel M, Fisher M, Warach S, Curram J, Teal P, Gregson B, Marler J, Claesson L, Bluhmki E, K. Muir and A. Shuaib
Gesehen am 17.03.2021